Quantification of systemic delivery of substrates for intermediate metabolism during citrate anticoagulation of continuous renal replacement therapy - Balik, Martin; Zakharchenko, Mykhaylo; Otahal, Michal; Hruby, Jan; Polak, Ferdinand; Rusinova, Katerina; Stach, Zdenek; Vavrova, Jaroslava; Jabor, Antonin (Blood purification, 2012)
BACKGROUND: There are limited data on systemic delivery of metabolic substrates during citrate anticoagulation. The direct citrate measurements are usually not available. METHODS: Patients on 2.2% acid-citrate-dextrose (ACD, n = 41) were compared to a control group on unfractionated heparin (n = 17). All were treated on 1.9-m(2) polysulfone filters. Samples were taken from the central venous catheter, ports pre- and post-filter and from effluent. RESULTS: The gain of citrate in CVVH (n = 18) was not different from CVVHDF (n = 23, p = 0.8). Mean gain of citrate was 25.4 ± 6.4 mmol/h. The systemic loads of lactate (p = 0.12) and glucose (p = 0.23) in CVVH were similar to CVVHDF. Mean inputs of lactate and glucose were 62.9 ± 21.1 and 26.6 ± 10.4 mmol/h, respectively. The mean difference between post- and prefilter unmeasured anions (d-UA) correlated with mean difference of citrate concentrations (p < 0.0001, r(2) = 0.66). The estimated caloric load of the citrate modalities was 5,536 ± 1,385 kJ/ 24 h. CONCLUSIONS: ACD might represent a significant load of metabolic substrates, particularly if used with lactate buffer. Systemic delivery of citrate can be predicted using d-UA in the extracorporeal circuit.
Keywords: glukosa; Acute Kidney Injury; design vybavení; kyselina mléčná; lidé; Citric Acid; Lactic Acid; Renal Replacement Therapy; kyselina citronová; Prospective Studies; Heparin; Equipment Design; náhrada funkce ledvin; antikoagulancia; Humans; prospektivní studie; Anticoagulants; akutní poškození ledvin; heparin; Glucose